Centralne repozytorium informacji publicznej - Gryszczyńska, Agnieszka (Kwartalnik Prawa Publicznego, 2012)
The subjects of the analysis are the legal provisions relating to the Central Repository of Public Sector Information, introduced by the amendments to the Law on Access to the Public Sector Information of 16 September 2011. The aim of Central Repository of Public Sector Information is to make available the public information of particular importance for the development of innovation in the state and the development of information society, which because of the way of its storing and sharing can be re-use, in a useful and effective way. The analysis of the adopted legislation concerning the Central Repository of Public Sector Information provokes reflection on the advisability of extracting an additional mode of making selected public information available, especially as the primary mode of access to information is the Public Sector Information Bulletin. Of note are the costs of establishment and maintenance of the Central Repository of Public Sector Information, the preparation of information resources for public as well as its verification and updating. Still there are no regulations that should specify in particular the information resources intended for placing in the Central Repository of Public Sector Information. Because of the quality of the data owned by public bodies and the expected costs of the Central Repository of Public Sector Information construction and maintenance, it is doubtful that the Central Repository of Public Sector Information will be able to guarantee validity, searchability and availability of the resource. Therefore, the most optimal solution would be the modernization of the existing Public Sector Information Bulletin.